1999
DOI: 10.1161/01.hyp.33.1.451
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged L-Arginine on Cardiovascular Mass and Myocardial Hemodynamics and Collagen in Aged Spontaneously Hypertensive Rats and Normal Rats

Abstract: Abstract-This study was designed to examine whether L-arginine could prevent hypertension-and age-related impairment of coronary hemodynamics and cardiac fibrosis in aged (80-week-old) rats. To differentiate between hypertension-and age-related changes, the study was performed in both normotensive Wistar-Kyoto rats (WKYs) and spontaneously hypertensive rats (SHR). Male 1-year-old rats of both strains were divided into 2 groups and given either placebo or L-arginine (1.2 g/L) in drinking water. After 6 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 42 publications
4
29
0
1
Order By: Relevance
“…We have also observed similar decreases in arterial pressure, total peripheral resistance, LV mass and collagen following prolonged L-arginine treatment, although RV collagen was not as decreased (39). These LV structural and functional improvements with L-arginine were observed only in SHR, suggesting that these endothelial dysfunctional changes in response to L-arginine were more related to hypertension than to aging.…”
Section: Ventricular Fibrosissupporting
confidence: 71%
See 1 more Smart Citation
“…We have also observed similar decreases in arterial pressure, total peripheral resistance, LV mass and collagen following prolonged L-arginine treatment, although RV collagen was not as decreased (39). These LV structural and functional improvements with L-arginine were observed only in SHR, suggesting that these endothelial dysfunctional changes in response to L-arginine were more related to hypertension than to aging.…”
Section: Ventricular Fibrosissupporting
confidence: 71%
“…These findings support the concept that local endothelial production of nitric oxide synthesis and endothelial dysfunction of the coronary circulation are thereby augmented. In addition, we have also reported that L-arginine administration also improves intracoronary hemodynamics and other pathophysiological alterations induced by hypertensive coronary vascular disease (39). Moreover, recent clinical studies have also shown that prolonged L-arginine treatment of patients with hypertensive or atherosclerotic vascular disease improves the associated clinical and hemodynamic alterations (40).…”
Section: Endothelial Dysfunctionmentioning
confidence: 84%
“…19 L-arginine supplementation improves the reduced vasodilatory response in offspring of hypertensive patients and in normotensive patients with familial essential hypertensive histories, suggesting that a genetic predisposition to essential hypertension involves a defect in NO generation. 9 Various aspects of the effect of L-arginine augmentation have been studied in human subjects, 20 --22 in animal experiments 23,24 and in tissue culture. 25 However, there is a dearth of epidemiological studies investigating ethnic differences in L-arginine utilisation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Mounting evidence suggests that this vascular impairment may be related to a diminished production and bioavailability of the potent vasodilator nitric oxide (NO), which may result from an increased vascular production of superoxide anion 2 or decreased endothelial levels of tetrahydrobiopterin 3,4 or L-arginine. 5 Interestingly, administration of NO precursor L-arginine restores endothelium-mediated vasodilatory function in patients with essential hypertension, 5 improves coronary hemodynamics in spontaneously hypertensive rats, 6 and increases NO production and reduces blood pressure in hypertensive rats with 7 or without 8 renal failure. These results suggest the possible reduction of L-arginine availability for NO synthesis in hypertension.…”
mentioning
confidence: 99%